2002
DOI: 10.1097/01.mp.0000032535.62750.d1
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity Associated with Uniparental Disomy in Breast Carcinoma

Abstract: Loss of heterozygosity is commonly assumed to be due to deletion of the appropriate genomic region in one chromosome within a neoplastic cell but may be due to other mechanisms such as mitotic nondisjunction or somatic recombination leading to uniparental heterodisomy. We chose to study the genomic regions surrounding the p53 and RB1 tumor suppressor genes in breast carcinoma to evaluate the different mechanisms that could mediate loss of heterozygosity. A microsatellite analysis of polymorphic markers in 50 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 40 publications
2
44
0
1
Order By: Relevance
“…Combined global analysis of LOH and genomic copy number data showed that LOH in PCa correlates positively to copy loss. Our data showed no signs of uniparental disomy in LOH regions, as otherwise recently reported to be a common mechanism in advanced breast cancer (Murthy et al, 2002;Cleton-Jansen et al, 2004), acute myeloid leukaemia , medullablastoma (Langdon et al, 2006) and basal cell carcinomas (Teh et al, 2005). Loss of heterozygosity and concomitant copy loss at chromosomes 8p, 10q, 13q,16q and 21q were found with an equal frequency in both localised and metastatic tumours, and were not associated with tumour stage or grade.…”
Section: Discussionsupporting
confidence: 77%
“…Combined global analysis of LOH and genomic copy number data showed that LOH in PCa correlates positively to copy loss. Our data showed no signs of uniparental disomy in LOH regions, as otherwise recently reported to be a common mechanism in advanced breast cancer (Murthy et al, 2002;Cleton-Jansen et al, 2004), acute myeloid leukaemia , medullablastoma (Langdon et al, 2006) and basal cell carcinomas (Teh et al, 2005). Loss of heterozygosity and concomitant copy loss at chromosomes 8p, 10q, 13q,16q and 21q were found with an equal frequency in both localised and metastatic tumours, and were not associated with tumour stage or grade.…”
Section: Discussionsupporting
confidence: 77%
“…Uniparental disomy or UPT are exceptional derivations of a pair of offspring chromosomes from one parent only (Engel, 1980) and cause an increased risk of recessive disorders, such as Wiedemann-Beckwith (Henry et al, 1991), Prader-Willi (Nicholls et al, 1989) and Angelman syndromes (Malcolm et al, 1991) owing to reduction to homozygosity (Engel, 1993). Furthermore, UPD regions have been shown to contain genes responsible for carcinogenesis, which have been implicated in Wilms' tumor (Grundy et al, 1994), leukemia (Raghavan et al, 2005) and breast cancer (Murthy et al, 2002), but have never been described in HCC. Our data showed that UPD is frequently observed on chromosome 6q, 10q and 13q, where LOH is observed repeatedly and contains suppressor genes, such as PTEN, DMBT1, BRCA2, RB and DLC2.…”
Section: Discussionmentioning
confidence: 99%
“…Allelic changes, including hemizygous deletion with a gain of the opposite allele, so-called uniparental disomy (UPD) or trisomy (UPT), are important in elucidating the molecular mechanisms of cancer (Engel, 1980). For example, accurate determination of the copy number of each allele separately in the UPD region, which may contain a region of methylation or null mutation of tumor suppressor genes, may allow the mechanism of carcinogenesis to be determined more clearly and comprehensively (Grundy et al, 1994;Murthy et al, 2002;Raghavan et al, 2005). In addition, accurate measurement of changes in copy number using high-resolution methods will help in the detection of heterogeneous populations among cancer cells (Benetkiewicz et al, 2005;Buckley et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of aUPD is nonrandom, varies within and between cancers, 15,29,30 and in leukemia is frequently associated with homozygous gene mutation. [20][21][22][23][24] In FL the mutational status of genes is less established and the secondary events more complex.…”
Section: Discussionmentioning
confidence: 99%